Population in industrialization. Ed. with an introd. by M. Drake. [Pref. by P. Mathias. With contribs by A.J. Coale, E.M. Hoover, K.H. Connell, a.o.] (Methuen etc., 1969)
With bibliogr., graph. and tabs. Debates in economic history. Gen. ed. Peter Mathias.